Impacts of climate change on ocular health: A scoping review - Yee Ling Wong; Shiao Wei Wong; Darren S.J. Ting; Alankrita Muralidhar; Sagnik Sen; Olivia Schaff; Hannah Istre-Wilz; Barbara Erny (Elsevier, 2024)
Climate change represents a significant global health crisis, characterized by a complex interplay of environmental shifts and interconnected phenomena. These alterations have given rise to a multitude of health implications, notably impacting ocular health. Our comprehensive review delineates a spectrum of eye conditions associated with climate change-related variables. Extremes in temperature and weather events have been observed to affect the ocular surface, resulting in an increased incidence of conjunctivitis, keratitis, dry eye disease, and pterygium. Furthermore, climate change is linked to a rising occurrence of cataracts, glaucoma, periocular tumors, and infections. Prolonged food insecurity, stemming from droughts, has been associated with nutritional optic neuropathies and consequent vision loss. Elevated temperatures have also been correlated with a heightened risk of retinal detachments necessitating urgent surgical intervention to enhance prognostic outcomes.This review also outlines the influence of climate-warming pollutants on a diverse array of eye conditions, manifesting as ocular surface infections, degenerative changes like pterygium, cataracts, refractive errors (myopia), blepharitis, meibomian gland infections, glaucoma, and vascular retinal occlusions.Mitigating the effects of climate change is an urgent global imperative necessitating collaborative efforts, encompassing research and education, to devise sustainable solutions that safeguard human health and well-being. This review seeks to delineate the current extent of available research, identify gaps in the existing literature, and chart the course for future studies in this intriguing association.